Convergence or Divergence? A Cluster Analysis of Energy Poverty Patterns Across the European Union Amidst Policy Shifts and Crises - Piotr Kosowski (Energies, 2025)
This paper investigates the dynamics of energy poverty across EU Member States from 2015 to 2023, a period characterized by economic recovery, the COVID-19 pandemic, and a significant energy crisis. Utilizing Eurostat EU-SILC data, the study analyzes trends in four key indicators: the inability to keep homes adequately warm, arrears on utility bills, housing cost overburden rate, and the at-risk-of-poverty rate. Data processing and trend analysis were performed using R and RStudio, while a k-means cluster analysis, executed in Python via Visual Studio Code, identified and compared distinct country groupings based on their energy poverty profiles in 2015 and 2023. The findings reveal a general improvement in energy poverty indicators across the EU until 2019, followed by a marked deterioration, particularly in energy affordability metrics post-2021 due to the energy crisis. This impact was observed to be distinct from general income poverty trends. While significant geographical disparities persist, with Southern and Eastern European countries often more vulnerable, the analysis also points to notable improvements in several Central and Eastern European nations. The cluster analysis, which identified eight clusters in 2015 and seven in 2023, suggests a degree of partial convergence. Key shifts include Poland’s transition to a lower-risk cluster and Spain’s move to a higher-risk group, while Southern Europe generally remains highly susceptible. This research underscores the dynamic and multifaceted nature of energy poverty, highlighting the necessity for targeted, context-specific policies. Addressing energy poverty is crucial for enhancing household resilience and achieving truly comprehensive energy security throughout the EU, especially amid the ongoing energy transition and potential future socio-economic shocks.